2023
DOI: 10.1371/journal.pcbi.1011047
|View full text |Cite
|
Sign up to set email alerts
|

Sequence similarity governs generalizability of de novo deep learning models for RNA secondary structure prediction

Abstract: Making no use of physical laws or co-evolutionary information, de novo deep learning (DL) models for RNA secondary structure prediction have achieved far superior performances than traditional algorithms. However, their statistical underpinning raises the crucial question of generalizability. We present a quantitative study of the performance and generalizability of a series of de novo DL models, with a minimal two-module architecture and no post-processing, under varied similarities between seen and unseen se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The sparsity of data alone could be responsible for the poor performance of deep learning methods dependent on millions of parameters to predict RNA structure, as it was seen at CASP15 [21, 22] for 3D structure prediction, as well as for 2D structure prediction [14, 15, 16, 17]. Other factors possibly handicapping the prediction of RNA structure are the more complex RNA backbone geometry that involves more atoms and degrees of freedom, as well as global nature of RNA secondary structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sparsity of data alone could be responsible for the poor performance of deep learning methods dependent on millions of parameters to predict RNA structure, as it was seen at CASP15 [21, 22] for 3D structure prediction, as well as for 2D structure prediction [14, 15, 16, 17]. Other factors possibly handicapping the prediction of RNA structure are the more complex RNA backbone geometry that involves more atoms and degrees of freedom, as well as global nature of RNA secondary structure.…”
Section: Discussionmentioning
confidence: 99%
“…The structural separation is needed in order to distinguish whether the methods are able to generalize to new structures or not; otherwise data leakage results in overfitting [18]. Recent studies of deep learning methods have also shown the need to separate structures between training and testing sets [14, 15, 16, 17, 23]. The goal of RNA3DB is to provide such structurally dissimilar grouping and splitting of the existing RNA 3D structures present in PDB.…”
Section: Comparison To Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were observed on the TORNADO dataset (see Supplementary Table 9 for details). The underlying reasons may be the susceptibility to overfitting of deep learning models, and the low data coverage and density over diverse structures, as discussed in earlier studies 66 , 67 . To address this challenge, potential solutions include: 1) Actively exploring the integration of inductive bias terms, such as statistical energy terms, into the KnotFold model; 2) Considering the implementation of more ensemble strategies to introduce greater diversity to the models.…”
Section: Discussionmentioning
confidence: 99%
“…This raises concerns about the generalizability of deep learning models trained on such limited data. Previous studies by Szikszai et al 39 and Qiu 40 highlighted the challenges of deep-learning models when applied to unseen families not present in the training and validation sets. To evaluate the adaptability of SPOT-RNA and SPOT-RNA2 beyond their training and validation data, we conducted a test by removing all test set structures with the structural similarity score (TM-score) ≥ 0.3 compared to those in the training and validation sets.…”
Section: Discussionmentioning
confidence: 99%